Depletion and Reversal of Hepatocellular Carcinoma Inducing CTL through ER Stress-Dependent PERK-CHOP Signaling Pathway - Mengnan Guo; Wei Wang; Wen Bai; Zekun Bai; Weixi Chen; Yali Su; Jinghua Wu (Canadian Journal of Gastroenterology and Hepatology)
Aims. In this report, it was investigated that hepatoma cells can cause downregulation of cytotoxic T lymphocyte (CTL) function and tea polyphenols (TPs) can reverse downregulation of CTL function. Methods. The expression of GRP78, PD-1, and TIM-3 was detected by western blotting in CTLL-2 cocultured with Hepa1-6 cells. Moreover, perforin (PRF1) and granzyme B (GzmB) protein levels and ER morphology were examined by ELISA and TEM, respectively. After 4-phenylbutyric acid (4-PBA) or tunicamycin (TM) treatment, programmed cell death protein 1 (PD-1), and mucin domain 3 (TIM-3), PRF1, and GzmB were measured by western blotting and ELISA. After sh-CHOP or GSK2656157 (PERK inhibitor) stimulation, the activation of the PERK-CHOP pathway was detected in CTLL-2 cells. Finally, changes in PD-1, TIM-3, PRF1, and GzmB levels were detected to verify the reversal of CTL depletion by TP. Results. The expression of GRP78, PD-1, and TIM-3 clearly increased, and swelling was observed for the endoplasmic reticulum (ER) in CTLL-2 cells cocultured with hepatoma cells. Concurrently, the levels of PRF1 and GzmB decreased. CTLL-2 depletion was induced after stimulation with TM and differed from 4-PBA stimulation. Treatment with sh-CHOP or GSK2656157 caused a decrease in PD-1 and TIM-3 expression, whereas the expression of PRF1 and GzmB clearly increased. After adding TP, the function of CTLs increased markedly. Conclusion. Hepatoma cells induced the depletion of CTLs through the ER stress PERK-CHOP pathway, and TP reversed this depletion by downregulating ER stress.